2010
DOI: 10.1002/clen.201000060
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Performance and Mechanism in Binding of Azo Dye by Raw Bentonite

Abstract: The adsorption behavior of methyl orange (MO) from aqueous solution onto raw bentonite (RB) sample was investigated as a function of parameters such as pH, inorganic anion, contact time, and temperature. The Langmuir and Freundlich adsorption models were applied to describe the equilibrium isotherms. Langmuir adsorption capacity was found to be 34.34 mg/g at pH 4.0. The pseudo-first-order, pseudo-secondorder kinetic, and the intra-particle diffusion models were used to describe the kinetic data. The values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…In this regards, multiple researchers studied the effectiveness of various type of clay in removing heavy metals from aqueous solutions including kaolinite (Sari et al 2007;Schaller et al 2009), bentonite (Ulmanu et al 2003;Kaya and Hakan Ö ren 2005;Eren et al 2009), illite (Ozdes et al 2011), sepiolite (Guerra et al 2010), montmorillonite (Lin and Juang 2002), and other adsorbents (Al-Degs et al 2006;Engates and Shipley 2011). Many other studies have been undertaken to evaluate the adsorptive capacity of various bioadsorbents in the removal of inorganic pollutants (Ahmad et al 2010;Das 2012;Dubey and Shiwani 2012;Revathi et al 2012;Eren 2010). They found that those cheap adsorbents could be used in the removal of different metal cations [e.g., Cd(II), Pb(II), Cu(II), Zn(II) … etc.].…”
Section: Introductionmentioning
confidence: 99%
“…In this regards, multiple researchers studied the effectiveness of various type of clay in removing heavy metals from aqueous solutions including kaolinite (Sari et al 2007;Schaller et al 2009), bentonite (Ulmanu et al 2003;Kaya and Hakan Ö ren 2005;Eren et al 2009), illite (Ozdes et al 2011), sepiolite (Guerra et al 2010), montmorillonite (Lin and Juang 2002), and other adsorbents (Al-Degs et al 2006;Engates and Shipley 2011). Many other studies have been undertaken to evaluate the adsorptive capacity of various bioadsorbents in the removal of inorganic pollutants (Ahmad et al 2010;Das 2012;Dubey and Shiwani 2012;Revathi et al 2012;Eren 2010). They found that those cheap adsorbents could be used in the removal of different metal cations [e.g., Cd(II), Pb(II), Cu(II), Zn(II) … etc.].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, MO sorption on raw bentonite decreased significantly from 34 to 8.1 and 7.5 when solution pH increased from 4.0 to 6.0 and then to 9.0 [10]. Meanwhile, the pseudo-second-order rate constant for the removal of MO by raw bentonite decreased from 0.04 to 0.01, and then to 0.007 g/mg-min, or 0.2, 0.04, and 0.02 kg/mmolmin at pH 4.0, 6.0, and 9.0 [10].…”
Section: The Effects Of Solution Ph and Ionic Strengthmentioning
confidence: 84%
“…Although raw MMT had limited affinity for acid dyes, acid activation could increase its MO sorption capacity by a factor of 8 [9]. A raw bentonite whose major mineral composition is MMT had an MO sorption capacity of 34 mg/g at pH 4 and the unusually large value was attributed to hydrogen bonding [10]. A similar MO sorption was found on another bentonite and was attributed to strong hydrophobic interaction [11].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Value of adsorption constant is noted as K 2 = 0.8728. Thus it can be interpreted that dye absorption by leather is better represented by Langmuir isotherm (Eran, 2010).…”
Section: Model Validationmentioning
confidence: 99%